Bond characteristics between concrete and near-surface mounted carbon fiber reinforced polymer cords. Issue 4 (2nd October 2021) - Obaidat, Yasmeen Taleb; Ashteyat, Ahmed M.; Taleb Obaidat, Ala'; Abu-Lebdeh, Muna N.
ABSTRACT: Previous studies showed that near-surface mounting (NSM) strengthening technique with rigid CFRP materials has potential advantages over the externally bonded reinforcing (EBR), therefore, it becomes efficient methodology for concrete strengthening. However, rigid NSM-CFRP cannot be wrapped around a deteriorated structural element; the need for the existence of flexible material has appeared. Therefore, in this study the flexible NSM-CFRP (cord) is investigated as strengthening technique instead of rigid NSM-CFRP. The aim of this study is to recognize the parameters affecting the bond performance of carbon fiber-reinforced concrete (CFRP) cord and concrete. These parameters are cords' bonded length, the ratio between cord's width and depth, concrete compressive strength, number of CFRP cords used and the distance separating cords in multi-cord specimens. Fifty-four concrete prisms were cast from 25 MPa and 50 MPa concrete compressive strengths. Thirtyeight prisms reinforced by a single cord with various cord sizes were prepared. Twelve and four specimens were reinforced with two and three cords, respectively. In the case of multi-cord specimens, a unified bond length and cord's aspect ratio were carried out. The main parameter to be studied in this case is the cords' separating spacing. The test results indicated that increasing (NSMCFRP) cords bonded length, concrete compressive strength, number of applied CFRP cords, the spacing between cords and reducing cords' aspect ratio (width/depth ratio) cause an increment in the pull-out force, and then a better strengthening is achieved. Rupture was the predominant failure mode for specimens with the same bond and equal cord dimension, while debonding of the CFRP cords is the most frequent failure mode for multi-cords specimens with greater spacing.